Pemberdayaan Masyarakat Lokal dalam Pengembangan Desa Wisata Cikolelet Berdasarkan Peraturan Daerah Kabupaten Serang Nomor 8 Tahun 2014 Tentang Rencana Induk Pembangunan Kepariwisataan Kabupaten Serang Tahun 2014-2025 - Sultan Cesar Khadafi; Ikomatussuniah Ikomatussuniah; Ahmad Lanang Citrawan (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines local community empowerment in the development of Cikolelet Tourism Village in Serang Regency based on Regional Regulation Number 8 of 2014 concerning the Master Plan for Tourism Development of Serang Regency 2014–2025. The development of tourism villages is intended to optimize cultural potential and local wisdom in order to enhance the economic and social welfare of the community, as well as to serve as a strategy for poverty alleviation through job creation and the strengthening of micro, small, and medium enterprises (MSMEs). The research focuses on the implementation of local community empowerment and the obstacles encountered in the development of the tourism village. This study employs the Theory of Development Law and the Welfare State Theory, using a juridical-empirical method with a descriptive qualitative approach. The findings indicate that community empowerment has been carried out through institutional establishment, basic tourism training, and community involvement in activities based on local potential. However, its implementation has not yet been optimal due to uneven community participation. Major constraints include limited funding, weak intersectoral coordination, low levels of community participation, and limited access to information and technology, which ultimately hinder the optimal development of community capacity.